Innovative Green Aviation: Strategic Management and Technological Advancements in Airport Ecosystems - Castillo Malagon, Romina; Alvarez Medina, Lourdes (ESI Preprints (European Scientific Journal, ESJ), 2025)
Adopting Sustainable Development Goals has driven significant changes in the aviation industry, and airport ecosystems are committed to minimizing their environmental impact. This article examines the sustainable strategies implemented within airport ecosystems and the associated technologies that support them. We develop a qualitative research approach anchored in documentary analysis and the theoretical framework of sustainable strategic management proposed by Stead and Stead (2004) that analyses sustainable strategies at a competitive and functional level. Strategies are defined from reports of airports certified with Level 5 of the Airport Carbon Accreditation program and official documents issued by non-governmental organizations and professional services firms such as KPMG, Deloitte, and McKinsey. The main strategies and technologies at a competitive level seek to reduce the carbon footprint by using renewable energy and electric vehicles, thus obtaining a cost advantage, and reducing resource depletion. Strategies and technologies that enable the exploitation of market opportunities are related to improving user experience and designing new routes using artificial intelligence. Total quality environmental management and environmental marketing strategies are relevant to primary activities, and the formation of infrastructure supporting long-term strategy stands out among the support activities. However, there is still a need for human resource management systems to have a sustainable vision. The aviation industry is known for its high level of complexity and the large number of actors involved in its operation, in this sense, using or developing technology and identifying its application in a concrete manner in the sustainable strategies of airports considered can favor the transition towards green aviation. Equally important is the formulation of public policies that encourage and support the transition towards decarbonization. However, it is the availability of financing the development of sustainable aircraft fuels, promoting research, technological developments, and the acquisition of machinery, equipment, and personnel training.